Demand for palm oil in the Balkans using autoregressive distributed lag (ARDL) - Kalsom Zakaria,; Jirsah A Bakar Kunchu,; Kamalrudin Mohamed Salleh,; Balu Nambiappan,; Nur Ain Mohd Hassan,; Abdul Hafizh Mohd Azam, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Demand for edible oils and fats in the Balkan countries shows an increasing trend, including the demand for palm oil. Imports of palm oil for this region are mainly sourced directly from major producing countries, namely Indonesia and Malaysia. The Balkan countries also import palm oil from non-palm oil producing countries like the Netherlands, Germany and Italy. This study differs from existing studies on palm oil demand as it focuses on palm oil demand specifically in the 4 countries of the Balkan Region. Therefore, the quarterly data from from 2008 to 2016 are used to examine the factors affecting demand for palm oil in the Balkans using, this study used autoregressive distributed lag (ARDL). The result of the bound test from 4 Balkan countries only in 3 countries shows that the studied variables and palm oil demand there is a long-run relationship. The countries are Bulgaria, Croatia and Greece. This study also shows that GDP, population and palm oil price have significant influence on the demand for palm oil in the Balkan countries.